Acceptor and Donor Dopants in Potassium Sodium Niobate Based Ceramics - Hussain, Fayaz; Khesro, Amir; Lu, Zhilun; Alotaibi, Nouf; Mohamad, Ahmad Azmin; Wang, Ge; Wang, Dawei; Zhou, Di (Frontiers in Materials, 2020)
B-site doping in potassium sodium niobate (KNN) with Mn2+(〖Mn〗_Nb^) and Ti4+ (〖Ti〗_Nb^) dopants were soluble but prevented KNN from achieving a high relative density while Sn4+(〖Sn〗_Nb^) was not soluble in the structure as evidenced by second phase peaks in XRD traces. However, SnO2 was an effective sintering aid in KNN-50/50. A-site doping with Sr2+(〖Sr〗_((Na,K))^•) up to 1 mol% initially improved density but higher sintering temperatures were required for compositions with > 1 mol% Sr. All Ti-doped and Sr-doped compositions showed an increase in conductivity, manifested as high values of dielectric loss (tanδ). More than 1% acceptor and donor dopants showed the ionic-type conduction mechanism while 1% behaved the electronic mechanism as attributed from the strongly frequency-dependent tanδ . Sample with 5% and 7% of Sr-doping completely shifted the transition of TO-T to below RT and broadened the TC peaks as the relaxor. In result, these samples have the potential to open the new application in the field of electroceramics.